2020
DOI: 10.1002/pchj.365
|View full text |Cite
|
Sign up to set email alerts
|

Perceived cognitive challenge predicts eye movements while viewing contemporary paintings

Abstract: Contemporary art is often challenging for the viewer, especially when it violates classic rules of representation. Also, viewers usually have little knowledge about this type of art, making its reception even more difficult. Our main research question was how the cognitive challenge associated with contemporary art affects eye movement. In particular, we aimed to assess the impact on eye movements of (a) object‐related cognitive challenge in terms of image properties (syntactic and semantic violations) and (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 70 publications
0
10
1
Order By: Relevance
“…Therefore, we can only speculate on the possible direction of the relationship between semantic violations/inconsistencies in titles and eye movements. Given that ambiguities make the processing more effortful (Ganczarek et al, 2020;Szubielska et al, 2021a) we could expect longer fixations, smaller saccade amplitudes and shorter durations. However, if we consider that semantic violations are related to multiple visual cues spread in different areas of paintings, we could also hypothesize that the saccade amplitudes will increase (Goldberg et al, 2002).…”
Section: Stationary Entropymentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we can only speculate on the possible direction of the relationship between semantic violations/inconsistencies in titles and eye movements. Given that ambiguities make the processing more effortful (Ganczarek et al, 2020;Szubielska et al, 2021a) we could expect longer fixations, smaller saccade amplitudes and shorter durations. However, if we consider that semantic violations are related to multiple visual cues spread in different areas of paintings, we could also hypothesize that the saccade amplitudes will increase (Goldberg et al, 2002).…”
Section: Stationary Entropymentioning
confidence: 99%
“…Also, they found that artworks' ambiguity predicted viewing time differently depending on the context: ambiguity was a positive predictor of viewing times in museums, but a negative one in a laboratory setting (Brieber et al, 2014). However, in a different study (in a laboratory setting) a positive relationship between subjectively experienced cognitive challenge (compound measure of ambiguity, complexity and inconsistency) and fixation durations, area of exploration and viewing time was found (Ganczarek et al, 2020). Therefore, longer careful fixations over large parts of paintings may be related to higher liking and greater understanding via a need to cognitively master artworks.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Art implies to see beyond physical reality, and perceive (implicitly or explicitly) the hidden structures or intents lying behind (Bao, Yang, et al, 2017;Rogala, Bajno, & Wróbel, 2020): this could be demonstrated by the observation that viewers are able to identify the original color or orientation of abstract paintings (Bao, Yang, et al, 2017;Lelièvre & Neri, 2019;Lindauer, 1987;Mather, 2012) and even the original perspective of portraits (Wang & Bao, 2020). Hidden syntax-like structures (or more generally, hierarchical structures) have been proposed for music (London, 2002;Patel, 2003;Pöppel, 1989;Wittmann & Pöppel, 1999), poetry (Teng et al, 2020;Turner & Pöppel, 1988;, and even visual arts (Ganczarek, Pietras, & Rosiek, 2020). This process would find its resemblance in perceiving the hierarchical structure of language and making pragmatic inferences.…”
mentioning
confidence: 99%